Reservoir property changes during CO2–brine flow-through experiments in tight sandstone: Implications for CO2 enhanced oil recovery in the Triassic Chang 7 Member tight sandstone, Ordos Basin, China. (1st August 2019) - Wu, Songtao; Zou, Caineng; Ma, Desheng; Zhai, Xiufen; Yu, Hongwei; Yu, Zhichao
Graphical abstract: The effects of supercritical CO2 (ScCO2 ) on reservoir property changes were investigated using CO2 –brine flow-through experiments which were set up based on the actual geological background. Inductively coupled plasma–atomic emission spectrophotometry (ICP-AES), quantitative evaluation of minerals with high-resolution scanning electron microscopy (QEMSCAN), computed tomography (CT) scanning, and physical property were adopted to develop an in situ 3D model to define porosity–mineral evolution. Variable mineral evolution, i.e., dissolution, migration, and re-precipitation of minerals and the related pore structural changes were described. All these findings have implications for the large-scale injection of CO2 into reservoirs during enhanced oil recovery (EOR) programs and for carbon capture, utilization, and storage (CCUS) programs. Highlights: In-situ mineral and pore evolution model during CO2 -brine-rock interaction are established. Main dissoluted and new generated minerals are classificated and quantitatively evaluated. Porosity changes are closely related to the total content of clay minerals. Main minerals for carbon sequestration and storage are investigated. Abstract: The effects of supercritical CO2 (ScCO2 ) on reservoir property changes of the Chang 7 Member tight sandstones of the Yanchang Formation, Ordos Basin, China, were investigated using CO2 –brine flow-through experiments, in conjunction with detailed rock and fluid characterization (pre- and post-experiment) using X-ray diffraction mineral analysis, 3D computed tomography scanning, high-resolution scanning electron microscopy, and inductively coupled plasma–atomic emission spectrophotometry. An in situ 3D model was developed to define porosity–mineral evolution. Experiments on three contrasting samples show that minerals such as potassium (K) feldspar, albite, and calcite are variably dissolved during CO2 –brine–mineral interactions. The dissolution, migration, and re-precipitation of clay minerals are common and are characterized by the dissolution of chlorite and the re-precipitation of kaolinite, calcium montmorillonite, and sodium montmorillonite. The original chlorite–kaolinite framework of the host rocks was destroyed. Precipitated and re-migrated clay particles (e.g., kaolinites and smectites) that were released by the dissolution accumulated in pore throats, resulting in changes to the pore system and in the physical properties of the host rocks. Physical property change pathways vary among the studied samples, with porosity being reduced by 4.5% and 12.8% or increased by 13.7% by the end of the experiments. Permeability reduction was 33.3%–81.2% and is positively correlated to host rock clay mineral content. The influence of the type and content of clay minerals on porosity requires further evaluation. The findings of the study have implications for the large-scale injection of CO2 into reservoirs during enhanced oil recovery programs and for carbon capture, utilization, and storage programs.